The First Philosophers of the Limensis Academy - Pretell García, Milko H. (2018)
The purpose of the following paper is to provide data on the development of philosophy in the first years of functioning of San Marcos University. To this end, the paper addresses, first, the development and importance of the Faculty of Arts; second, the course of studies designed for the study of philosophy; and, last, the required steps to become a lector. The paper closes with a list of the first philosophy lectores of San Marcos University.